Role of market orientation in sustainable performance: The case of a leading microfinance provider. Issue 3 (8th August 2016) - Kazemian, Soheil; Abdul Rahman, Rashidah; Mohd Sanusi, Zuraidah; Adewale, Abideen A.
Abstract : Purpose: Without prejudice to the efficacy of other poverty alleviation mechanisms, micro-financing arguably enjoys relative prominence. However, notwithstanding the remarkable loan repayment rate that the microfinance firms report, they still face the challenge of sustainability. The paper aims to provide insights into how three dimensions of market orientation, namely, customer orientation, competitor orientation and inter-function coordination, affect the two aspects of the sustainability of microfinance institutions (MFIs; management and financial). Design/methodology/approach: To achieve this goal, this study focuses on Amanah Ikhtiar Malaysia (AIM), a leading microfinance provider which is also the largest MFI in South East Asia. Data elicited via a survey questionnaire administered on 190 management staff of AIM across Malaysia are subjected to statistical analysis via the partial least square-structural equation modeling using SmartPLS 2.0. Findings: The results provide empirical evidences that indicate that management sustainability is significantly influenced by customer orientation and inter-function coordination. However, only customer orientation affects the financial sustainability of AIM. Nevertheless, competitor orientation has non-significant effects on both aspects of sustainability of AIM. Research limitations/implications: The result of the paper contributes to the literature in understanding the long-term sustainable financial and social performance-based market orientation. Originality/value: Findings are useful for policy makers, management of MFIs, practitioners and academics to enhance microfinance system. Managerial implications, limitation of the study and suggestions for future research are also included.